The Influence Hand Eye Coordination and Student Learning Dicipline on the Basic Vollyball Technique Skills of Students Of SMP - Yona Evasari; Kamal Firdaus; Syafruddin Syafruddin; Hastria Efendi (STKIP Muhammadiyah Kuningan, 2023)
This study aimed to see the effect of aerobic endurance, hand-eye coordination, and learning discipline on essential volleyball skill items for SMP N 2 North Lintau Buo. This type of research is path analysis (fat analysis) with the variables of aerobic endurance, eye-hand coordination, and learning discipline. The population of this study was 20 grade VIII students of SMP N 2 Lintau Buo Utara. The sampling technique in this study was purposive, so 20 students were randomly selected as the sample at SMP N 2 Lintau Buo Utara. The grouping of samples is random. Data collection was carried out by testing basic volleyball skills, namely passing over, under, serve and serve over. The data was then analyzed by t-test. The study results can be concluded that there is a significant influence between hand-eye coordination and learning discipline in students playing volleyball. This is seen from the results of the data analysis sig value <0.05. So, hand-eye coordination and learning discipline are essential in volleyball.